DISSOLUTION KINETICS AS A FUNCTION OF THE GIBBS FREE ENERGY OF REACTION: AN EXPERIMENTAL STUDY BASED ON ALBITE FELDSPAR - Hellmann R.; Tisserand D. (My University, 2006)
Here we report on an experimental investigation of the relation between the dissolution rate of albite feldspar and the Gibbs free energy of reaction, ΔGr. The experiments were carried out in a continuously stirred flow-through reactor at 150 °C and pH(150°C) 9.2. The dissolution rates R are based on steady-state Si and Al concentrations and sample mass loss. The overall relation between ΔGr and R was determined over a free energy range of -150 < ΔGr < -15.6 kJ mol-1. The data define a continuous and highly non-linear, sigmoidal relation between R and ΔGr that is characterized by three distinct free energy regions. The region furthest from equilibrium, delimited by -150 < ΔGr < -70 kJ mol-1, represents an extensive dissolution rate plateau with an average rate R̄ = 1.0 × 8 mol m-2 s-1. In this free energy range the rates of dissolution are constant and independent of ΔGr, as well as [Si] and [Al]. The free energy range delimited by -70 ≤ ΔGr ≤ - 25 kJ mol-1, referred to as the 'transition equilibrium' region, is characterized by a sharp decrease in dissolution rates with increasing ΔGr, indicating a very strong inverse dependence of the rates on free energy. Dissolution nearest equilibrium, defined by ΔGr > -25 kJ mol-1, represents the 'near equilibrium' region where the rates decrease as chemical equilibrium is approached, but with a much weaker dependence on ΔGr. The lowest rate measured in this study, R = 6.2 × 10-11 mol m-2 s-1 at ΔGr = -16.3 kJ mol-1, is more than two orders of magnitude slower than the plateau rate. The data have been fitted to a rate equation (adapted from Burch et al. [Burch, T. E., Nagy, K. L., Lasaga, A. C., 1993. Free energy dependence of albite dissolution kinetics at 80 °C and pH 8.8. Chem. Geol. 105, 137-162]) that represents the sum of two parallel reactions R = k1 [1- exp(-ngm1)] + k2[1 - exp(-g)]m2, where k1 and k2 are rate cons tants that have been determined by regression, with values 1.02 × 10-8 and 1.80 × 10-10 mol m-2 s-1, g ≡ ΔGr /RT is a dimensionless number, and n, m1, and m2 are adjustable fitted parameters (n = 7.98 × 10-5, m1 = 3.81 and m2 = 1.17). Based on measurements of the temporal evolution of RSi and RAl for each experiment, steady-state dissolution rates appear to be congruent at all ΔGr. In contrast, non-steady-state dissolution is incongruent, and is related to ΔGr. Scanning electron microscopy (SEM) images of post-reaction grain surfaces indicate that dissolution close to equilibrium (ΔGr > -25 kJ mol-1) resulted in the precipitation of a secondary crystalline phase, but there are no indications that this altered the measured R-ΔGr relation. © 2005 Elsevier Inc. All rights reserved.